2015
DOI: 10.1681/asn.2014030317
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Inhibition of Sodium-Hydrogen Exchanger 3 Reduces Phosphorus Absorption and Protects against Vascular Calcification in CKD

Abstract: In CKD, phosphate retention arising from diminished GFR is a key early step in a pathologic cascade leading to hyperthyroidism, metabolic bone disease, vascular calcification, and cardiovascular mortality. Tenapanor, a minimally systemically available inhibitor of the intestinal sodium-hydrogen exchanger 3, is being evaluated in clinical trials for its potential to (1) lower gastrointestinal sodium absorption, (2) improve fluid overload-related symptoms, such as hypertension and proteinuria, in patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 36 publications
2
72
0
Order By: Relevance
“…However, tenapanor is able to effectively reduce serum phosphate concentration, despite having no direct effect on NPT2b 23,24 and without directly binding intestinal phosphate. Studies in healthy volunteers and patients with CKD stage 5D have shown that tenapanor treatment increased stool sodium 23,25,26 and phosphorus 26 content, and concomitantly, it reduced urinary sodium 23,26 and phosphorus content, 26 consistent with reduced sodium and phosphate absorption.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, tenapanor is able to effectively reduce serum phosphate concentration, despite having no direct effect on NPT2b 23,24 and without directly binding intestinal phosphate. Studies in healthy volunteers and patients with CKD stage 5D have shown that tenapanor treatment increased stool sodium 23,25,26 and phosphorus 26 content, and concomitantly, it reduced urinary sodium 23,26 and phosphorus content, 26 consistent with reduced sodium and phosphate absorption.…”
Section: Discussionmentioning
confidence: 93%
“…Tenapanor acts in the gut to reduce the absorption of sodium and phosphate, with minimal systemic drug exposure. [23][24][25][26] In healthy volunteers, increases in stool phosphorus up to 14.2 mmol/d relative to placebo were observed with tenapanor dosing, with concomitant reductions in urinary phosphorus. 26 The mechanism by which tenapanor reduces GI phosphate uptake is under active investigation; it does not seem to involve direct inhibition of intestinal phosphate transporters type 1 or sodium-dependent phosphate transport protein 2B (NaPi2b, also known as NPT2b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When an inhibitor of intestinal sodium-hydrogen exchanger-3 that also blocked dietary phosphate absorption 78 was administered to rats with CKD, it decreased urinary phosphate excretion, reduced serum phosphate and FGF23 levels, attenuated vascular calcification, and reduced heart mass. 79 Nicotinamide may also promote phosphaturia. Intra-peritoneal delivery of nicotinamide increased urinary phosphate excretion without changing urinary excretion of creatinine, potassium, sodium, calcium, or urinary flow rates in rats.…”
Section: Phosphate Bindersmentioning
confidence: 99%
“…A study has demonstrated that this compound is also able to reduce phosphate uptake and reduce ectopic calcification in an animal model of CKD. 150 These novel drugs, particularly in combination with established therapies such as phosphate binders, might contribute to the future management of dysregulated phosphate homeostasis in patients with CKD, and possibly also in renal transplant recipients.…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%